2009
DOI: 10.1111/j.1467-9469.2009.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Likelihood Confidence Intervals for Response Mean with Data Missing at Random

Abstract: A kernel regression imputation method for missing response data is developed. A class of bias-corrected empirical log-likelihood ratios for the response mean is defined. It is shown that any member of our class of ratios is asymptotically chi-squared, and the corresponding empirical likelihood confidence interval for the response mean is constructed. Our ratios share some of the desired features of the existing methods: they are self-scale invariant and no plug-in estimators for the adjustment factor and asymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Xue [19] constructed a weight-corrected empirical log-likelihood ratio for θ 0 , which is also asymptotically chi-squared. Now, let us consider the following functions, constructed using the reconstituted response:…”
Section: Reconstitution Of the Response Variablementioning
confidence: 99%
“…Xue [19] constructed a weight-corrected empirical log-likelihood ratio for θ 0 , which is also asymptotically chi-squared. Now, let us consider the following functions, constructed using the reconstituted response:…”
Section: Reconstitution Of the Response Variablementioning
confidence: 99%
“…When some Y i 's are missing, even if we modify the function sans-serifg( X , Y , θ ) in to address the missing values, Wilks's theorem may break down unless a particular modified sans-serifg is used in . For example, when missingness is ignorable, that is, the propensity P ( δ = 1 | X , Y ) = π ( X ) is a function of X only, where δ is the indicator of whether Y is observed, Xue () showed that Wilks's theorem holds if sans-serifgfalse(X,Y,θfalse) in is replaced by truesans-serifg^false(X,Y,δ,θfalse)=δsans-serifgfalse(X,Y,θfalse)trueπ^false(Xfalse)δtrueπ^false(Xfalse)trueπ^false(Xfalse)truem^sans-serifgfalse(X,θfalse), where trueπ^false(Xfalse) and truem^sans-serifgfalse(X,θfalse) are nonparametric regression estimators of π ( X ) and msans-serifg( X , θ ) = E { sans-serifg( X , Y , θ ) | X , δ = 1}, respectively. It was also shown that if we omit the second term on the right‐hand side of , then Wilks's theorem does not hold, although using such a truesans-serifg^ in leads to an asymptotically valid estimator of θ 0 .…”
Section: Wilks Phenomenonmentioning
confidence: 99%
“…In the following simulations, the kernel function K(·) is taken to be K(t) = 3 4 (1 − t 2 ), if |t| ≤ 1, 0 otherwise, L(·) and Q(·) are taken to be K 1 (y)K 2 (v) with K 1 (y) = 15 16 (1 − y 2 ) 2 if |y| ≤ 1, 0 otherwise and K 2 (v) = − 15 8 v 2 + 9 8 if |v| ≤ 1, 0 otherwise. The bandwidths are taken to be b = h 2 = 3 5 n −1/6 and h = h 1 = 2 7 n −1/5 , which satisfy Condition (C5).…”
Section: Simulationsmentioning
confidence: 99%
“…They also considered the case with auxiliary information and defined an empirical likelihood-based estimator. Xue [16] reexamined the problem of empirical likelihood for the mean of Y in the situation with missing data. They proposed a class of bias-corrected empirical log-likelihood ratios and showed that any member of their class of ratios is asymptotically chi-squared and avoided the plug-in estimators for the adjustment factor and asymptotic variance.…”
Section: Introductionmentioning
confidence: 99%